EFFECTS OF COMMUNITY CONFLICTS ON RURAL ECONOMIC ACTIVITIES IN OSUN STATE, NIGERIA: IMPLICATIONS FOR SUSTAINABLE DEVELOPMENT - Alabi, D L; Famakinwa, M (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2017)
Conflict is a major impediment of any community development. However, its occurrence is inevitable and requires serious attention from relevant stakeholders. This study focused on the effects of community conflicts on rural economic activities in Osun State, Nigeria. It specifically unveiled the socio-economic characteristics of the respondents; identified the causes of conflict in the study area; determined the effects of conflicts on the economic activities and identified the strategies adopted in resolving the conflicts. Ninety community members were randomly sampled and interviewed. Both quantitative and qualitative data were collected using interview schedule and Key Informant Interview respectively. Data were analysed using appropriate descriptive and inferential statistical tools. The results showed that majority (77.6%) of the respondents were married with the mean age of 43.7 years and above half (52.6%) were males with the mean years of schooling of 10.1 years. Boundary dispute (85.5%), political tussle (82.2%) among community partisans, chieftaincy dispute (77.8%), competition of community members over limited resources (74.4%) and issues related to payment of tributes (70%) were the major causes of conflict. The effects of conflicts identified include loss of properties (mean=2.23), reduction in income (mean=2.23), disruption of economic activities (mean=2.22) and loss of employment (mean=2.10) among others. The study concluded that preventive measures against future conflict such as advocacy for tolerance and sensitivity of government to people’s needs should be put in place to enhance sustainable development.